Activity Trends of Binary Silver Alloy Nanocatalysts for Oxygen Reduction Reaction in Alkaline Media. Issue 15 (2nd February 2017) - Wu, Xiaoqiang; Chen, Fuyi; Zhang, Nan; Lei, Yimin; Jin, Yachao; Qaseem, Adnan; Johnston, Roy L.
Abstract : The electrocatalytic activity of Pt‐based alloys exhibits a strong dependence on their electronic structures, but a relationship between electronic structure and oxygen reduction reaction (ORR) activity in Ag‐based alloys is still not clear. Here, a vapor deposition based approach is reported for the preparation of Ag75 M25 (M = Cu, Co, Fe, and In) and Ag x Cu100− x ( x = 0, 25, 45, 50, 55, 75, 90, and 100) nanocatalysts and their electronic structures are determined by valence band spectra. The relationship of the d‐band center and ORR activity exhibits volcano‐shape behaviors, where the maximum catalytic activity is obtained for Ag75 Cu25 alloys. The ORR enhancement of Ag75 Cu25 alloys originates from the 0.12 eV upshift in d‐band center relative to pure Ag, which is different from the downshift in the d‐band center in Pt‐based alloys. The activity trend for these Ag75 M25 alloys is in the order of Ag75 Cu25 > Ag75 Fe25 > Ag75 Co25 . These results provide an insight to understand the activity and stability enhancement of Ag75 Cu25 and Ag50 Cu50 catalysts by alloying. Abstract : The oxygen reduction reaction (ORR) activity trends of binary silver alloy nanocatalysts are discussed, which are highly dependent on the d‐band center of valence band spectrum. The results present that the upshift d‐band center is beneficial for ORR and the optimal Ag50 Cu50 catalyst (0.1 eV) shows high activity and durability for ORR in alkaline media, which is comparable to the commercial Pt/C‐20% catalyst.